(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2024)
Preservation of digestive structures in trilobites is generally rare; remains of the alimentary tract have been documented in about eighty of more than twenty thousand described species. Several tens of specimens belonging to five Cambrian and nine Ordovician species from the Barrandian area, Czech Republic, have markedly contributed to the knowledge of the trilobite digestive system. Here, we describe seven exceptionally preserved late holaspid trilobite specimens of species of the genus Dalmanitina collected from Upper Ordovician strata of the Barrandian area. All studied specimens are preserved as internal moulds and exhibit a narrow strip-like structure that runs sagitally or sub-sagitally under the axial lobe of the thoracopygon. These strip-like structures are markedly different from scavenger burrows and are interpreted as remains of the alimentary canal. A slightly expanded anterior-most part of the digestive system is preserved in the cephalic shield of six specimens and is interpreted as a remainder of the anterior midgut. A dark area is seen in the glabellar lobes of three specimens. These dark areas do not represent pyrite concentrations in the hypostome–glabellar cavity, because they contain only small amounts of Fe and S. These areas are interpreted as the remainder of cephalic digestive midgut diverticula, or the “perigastric organ”. Quantitative chemical analyses show that in species of Dalmanitina the digestive system is preserved as dark matter containing partly digested food particles and most probably also a higher amount of clay minerals. The described specimens constitute the first well-documented example of digestive structures in the subfamily Dalmanitininae.